Impact of glutathione supplementation of parenteral nutrition on hepatic methionine adenosyltransferase activity - Elremaly, Wesam (Redox Biol, 2015)
BACKGROUND: The oxidation of the methionine adenosyltransferase (MAT) by the combined impact of peroxides contaminating parenteral nutrition (PN) and oxidized redox potential of glutathione is suspected to explain its inhibition observed in animals. A modification of MAT activity is suspected to be at origin of the PN-associated liver disease as observed in newborns. We hypothesized that the correction of redox potential of glutathione by adding glutathione in PN protects the MAT activity. AIM: To investigate whether the addition of glutathione to PN can reverse the inhibition of MAT observed in animal on PN. METHODS: Three days old guinea pigs received through a jugular vein catheter 2 series of solutions. First with methionine supplement, (1) Sham (no infusion); (2) PN: amino acids, dextrose, lipids and vitamins; (3) PN-GSSG: PN+10 μM GSSG. Second without methionine, (4) D: dextrose; (5) D+180 μM ascorbylperoxide; (6) D+350 μM H(2)O(2). Four days later, liver was sampled for determination of redox potential of glutathione and MAT activity in the presence or absence of 1 mM DTT. Data were compared by ANOVA, p<0.05. RESULTS: MAT activity was 45±4% lower in animal infused with PN and 23±7% with peroxides generated in PN. The inhibition by peroxides was associated with oxidized redox potential and was reversible by DTT. Correction of redox potential (PN+GSSG) or DTT was without effect on the inhibition of MAT by PN. The slope of the linear relation between MAT activity and redox potential was two fold lower in animal infused with PN than in others groups. CONCLUSION: The present study suggests that prevention of peroxide generation in PN and/or correction of the redox potential by adding glutathione in PN are not sufficient, at least in newborn guinea pigs, to restore normal MAT activity.